In vitro antagonism of rhizospheric fluorescent pseudomonads of coconut against Ganoderma applanatum and Thielaviopsis paradoxa, fungal pathogens of coconut - George, Priya; Gupta, Alka; Gopal, Murali; ChandraMohanan, R.; Thomas, Litty; Thomas, George V. (Journal of Plantation Crops, 2012)
A total of 156 fluorescent pseudomonads were tested for antagonistic activity towards G. applanatum and T. paradoxa in a dual-plate assay on King’s B agar plates. Eight percent of the total fluorescent pseudomonads showed antagonism towards G. applanatum (inhibition ranging from 39% to 73%) and 16% of the isolates inhibited T. paradoxa in the range of 20% - 76%. Moreover, eight percent of the fluorescent pseudomonads significantly inhibited both pathogens tested. They were found to possess some important biocontrol traits such as HCN, siderophores, ammonia and antibiotics. Among them fluorescent Pseudomonas spp. KiSF 17 and KiSF 16 exhibited strong antagonistic activity. They were identified as P. aeruginosa by Biolog® GEN III microplate identification system and confirmed by 16S rDNA sequencing. The present studies revealed the survival of useful bacterial antagonists in the rhizosphere of coconut palm, which have the potential to be used as a biocontrol agent.